AL-HAQAIQ AL-INSANIYYAH FI MUKHTARATI AL-SYI’RI “PERJAMUAN KHONG GUAN” LI JOKO PINURBO BI AL-MANDZUR LUCIEN GOLDMANN - Asy’syifa, Diah Nur; Damayanti, Afifah Fadia; Yurisa, Penny Respati; Roziki, Khafid (Annual International Conferences on Language, Literature, and Media, 2023)
This study aims to express human facts in the form of descriptive data that characterize or describe conditions, situations, or phenomena contained in the poetry anthology of Perjamuan Khong Guan by Joko Pinurbo. The primary data source for this research is data obtained by the research source, namely Joko Pinurbo's poetry anthology Perjamuan Khong Guan, published by Gramedia Pustaka. To examine the data obtained, the collection techniques used in this study were reading techniques and note-taking techniques. The data validation technique in this study was carried out by testing the accuracy of the data through three stages, including: Data triangulation is defined as checking the credibility of data from various sources, techniques, and various times. The results of this study reveal the theme of human facts in Joko Pinurbo's anthology of poetry Perjamuan Khong Guan. Three important observations emerge from the results of the analysis: (1) the image of alienation in the relationship between the individual and religion, family and social environment; (2) feelings of being marginalized and losing identity in the context of democracy and politics; (3) describes the celebrations that take place behind a wasteful and brutal democratic system. The results of this study indicate that there is a relationship between the anthology variables of the poem "Khong Guan Supper" and the theory of human facts from the perspective of Lucien Goldmann. The poems in this poetry anthology describe the experiences of every individual who experiences dissatisfaction, either by religion, family, politics or the social environment.